Washington wines and wineries : the essential guide - Gregutt, Paul (University of California Press, 2010)
During the thirty-five years wine critic and writer Paul Gregutt has lived in the state of Washington, its wine industry has ballooned from a mere half dozen wineries to nearly five hundred. Washington Wines and Wineries offers a comprehensive, critical, and accessible account of the nation's second largest wine-producing region.